Forced Rohingya Migration: as Challenge for Global Government and Islamic Organization in Giving Resolution - Muhammad Ulul Albab (Jayapangus Press, 2022)
This research discusses how Islamic perspective and the global regime with the United Nations of the High Commission for Refugee (UNHCR) as an international organization responsible for global refugees can give solution and handle victims of forced migration experienced by ethnic Muslim Rohingya, so a question for this research is “What are Global Government and Islamic Organization on providing solutions to Rohingya forced migration in the International World?”. This is based on the ethnic cleansing efforts carried out by unscrupulous Buddhists as Myanmar community majority against Rohingya Muslim minority ethnic groups who are in Rakhine State. The ethnic cleansing efforts undertaken by ethnic Buddhists against Muslim ethnicity have become the spotlight for the international world which is a violation of human rights that occurred in it and questioned the state's responsibility in handling the case. UNHCR as an international organization responsible for refugees has a difficult task in carrying out their duties due to the increasing number of global migration crises. Forced Migration is one of the victims of human rights violations which is strictly prohibited in Islamic teachings. Human rights violations are prohibited by Islam because they take away some of the rights that should be possessed by each individual. In this case, how then Islam and the global regime provide a solution to the forced migration experienced by ethnic Rohingya Muslims. In this research, qualitative research used by library studies to identify the problem in this paper, and also human security as theoretical framework to look how the world give solutions for Rohingya migrations. From this research, global government (UNHCR) and Islamic organization look that Rohingya migrations are the forced migration which need asylum for their life, so global government give them identity for surviving.